2011
DOI: 10.1177/0192513x11412497
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Support in Family Relationships After Hurricane Katrina

Abstract: In this article, the authors merge the study of support, strain, and ambivalence in family relationships with the study of stress to explore the ways family members provide support or contribute to strain in the disaster recovery process. The authors analyze interviews with 71 displaced Hurricane Katrina survivors, and identify three family relationships that were especially important to postdisplacement experiences: marital or intimate partner, parent-adult child, and fictive kin. These relationships provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…For instance, Reid and Reczek (2011) examined the effect of marital status on the recovery process after Hurricane Katrina and found that relationships with their marital or intimate partner influenced the recovery of Katrina survivors, although the pattern was inconsistent. Some survivors experienced the relationship with their partners as a source of support, whereas for others it contributed to the stress associated with recovery.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Reid and Reczek (2011) examined the effect of marital status on the recovery process after Hurricane Katrina and found that relationships with their marital or intimate partner influenced the recovery of Katrina survivors, although the pattern was inconsistent. Some survivors experienced the relationship with their partners as a source of support, whereas for others it contributed to the stress associated with recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Social networks are crucial conduits of emotional and instrumental support that buffers against psychological distress in the short-term after disaster and aids psychological recovery in the long-term (Barnshaw & Trainor, 2006; Galea et al, 2005; Hurlbert, Haines, & Beggs, 2000; Reid & Reczek, 2011). Research demonstrates that perceived emotional social support is protective against psychological disorders (Adeola & Picou, 2014; Charuvastra & Cloitre, 2008; Paxson, Fussell, Rhodes, & Waters, 2012; Weems et al, 2007), while network disruption and loss of support is positively associated with risk of PTSD (Fredman et al, 2010; Hall et al, 2014; Hall, Murray, Galea, Canetti, & Hobfoll, 2015).…”
Section: Network Disruption and Function After Natural Disastermentioning
confidence: 99%
“…Bolin and Stanford () make an important distinction between availability and accessibility of post‐disaster assistance: while there may be much assistance available, as was the case following the Northridge earthquake, the formal qualification criteria of various assistance programs, combined with pre‐disaster inequalities, make it more difficult for marginalized populations to access assistance. Proving that one is truly a disaster victim in real need of assistance is often a cumbersome and time‐consuming task (Reid in press; Reid and Reczek ). Bolin and Stanford point out that there is an explicit intent on the part of governmental assistance programs to only return people to their pre‐disaster conditions, not to improve them.…”
Section: Recent Research On Inequalities and Disastermentioning
confidence: 99%
“…Research into the poor governmental response to Hurricane Katrina suggests that both institutional and interpersonal racism were major factors in this response and continued to negatively impact the post‐disaster recovery assistance experience (Chamlee‐Wright and Storr ; Giroux ; Nguyen ; Pyles ; Reid in press; Reid and Reczek ). A study of a community‐based action research project revealed that racism was a major problem in the practice of applying an international non‐governmental organization's recovery policies (Pyles ).…”
Section: Recent Research On Inequalities and Disastermentioning
confidence: 99%